Extratos de cerejeira-do-rio-grande (Eugenia involucrata): avaliação da bioatividade em modelos in vitro - Smaniotto, Franciele Aline (2022)
Eugenia involucrata DC. is an underexplored native plant species, found in the Southern and Southeastern regions of Brazil. Recent studies report the presence of large amounts of phenolic compounds that potentially benefit human health in different parts (leaves, pulp, and seeds) of this species. Diabetes is characterized by hyperglycemia, which results in the glycation of proteins and excessive generation of reactive oxygen species (ROS) that lead to oxidative stress and the formation of advanced glycation end products (AGEs). Thus, one of the strategies for the treatment and/or protection of diabetes is to promote the reduction of blood glucose levels, through the inhibition of enzymes involved in carbohydrate digestion. So far, no study has been found in the literature on the effects of extracts from the pulp and seed E. involucrata towards enzymes involved in the digestion of carbohydrates and lipids. Therefore, the aim of this study was to investigate in vitro the anti-hyperglycemic and anti-obesogenic potential of phenolic compounds of ethanolic extracts from E. involucrata pulp and seed, through their ability to inhibit enzymes involved in the digestion of carbohydrates and lipids, and to evaluate the inhibition of AGEs formation, and the potential ability to neutralize reactive species of biological importance. The seed extract had higher content of total phenolic compounds (11,550.5 ± 633.0 µg. mL-1 ), being composed of phenolic acids and flavonoids, than the pulp extract (440.7 ± 28.1 µg. mL-1 ) that was composed of phenolic acids, flavonoids and anthocyanins. The IC50 values (µg of phenolic compounds. mL-1 ) revealed that the extracts had higher potency than acarbose towards the inhibition of α-amylase (0.2 ± 0.0 for pulp; 1.3 ± 0.2 for seed; 39.9 ± 3.9 for acarbose) and α-glucosidase (0.3 ± 0.0 for pulp; 1.5 ± 0.0 for seed; 2,019.0 ± 81.3 for acarbose), but lower potency than orlistat to inhibit pancreatic lipase (0.7 ± 0.0 for pulp; 0.6 ± 0.0 for seed; 0.1 ± 0.0 for orlistat). Extracts also inhibited (IC50 values as µg of phenolic compounds. mL-1 ) the formation of AGEs (6.8 ± 0.3 for pulp; 30.9 ± 1.7 for seed; 256.6 ± 13.7 for aminoguanidine) and were able to remove free radical species of biological relevance, namely peroxyl radical (0.02 ± 0.0 for pulp; 0.12 ± 0.0 for seed), hydroxyl radical (3.9 ± 0.0 for pulp; 4.5 ± 0.1 for seed). Despite the higher potency of phenolic compounds extracted from E. involucrata pulp towards all biological effects investigated when compared to the phenolics from seed extract, seed extraction has greater yield. Therefore, the concentration of phenolic compounds was 26 times higher in seed than pulp extract and seed extract had higher potency than pulp extract when taking into account the amount of pulp or seed that is necessary to obtain each extract. The results obtained in this study provide a basis for further studies in animal models and clinical studies for the development of new drugs or nutraceuticals, as well as food products with functional properties.